Effectiveness of Rashtriya Swasthya Bima Yojana : A Case Study in Rural West Bengal, India - Bose, Mampi (Arthshastra Indian Journal of Economics & Research, 2018)
Rationale: Out of pocket expenditure on health, as share of total health expenditure, is very high in India. High expenditure on health has a negative impact on households' economic and health conditions. In order to reduce expenditure and improve utilization of healthcare services, the Government of India launched an insurance scheme, Rashtriya Swasthya Bima Yojana (RSBY) in 2008. The paper intended to find how successful the scheme has been in terms of reducing out of pocket expenditures and improving institutional delivery. Data & Method : Primary data were used to analyze the effectiveness of the scheme in terms of reducing out of pocket expenditures. I followed multistage sampling method to collect data. Data was collected in 2014 taking 2 years as reference period. Around 251 households were surveyed using a semi structured questionnaire. I used the propensity score matching model to analyze the effectiveness. Findings : The scheme failed to achieve its goals. The scheme did not prove to be inclusionary in nature and suffered from several pitfalls at different stages of its implementation.